Excitonic interactions in the reaction centre of photosystem II studied by using circular dichroism - Vácha, Frantisek; Durchan, Milan; Siffel, Pavel (Biochimica et biophysica acta, 2002)
Changes in excitonic interactions of photosystem II (PSII) reaction centre (RC) pigments upon light-induced oxidation of primary donor (P680) or reduction of primary acceptor (pheophytin (Pheo)) were analysed using circular dichroism (CD). The CD spectrum of PSII RC shows positive bands at 417, 435 and 681 and negative bands at 447 and 664 nm. Oxidation of the primary donor by illuminating the sample in the presence of silicomolybdate resulted in nearly symmetric decrease of CD amplitudes at 664 and 684 nm. In the Soret region, the maximum bleaching of CD signal was detected at 449 and 440 nm. Accumulation of reduced Pheo in the presence of dithionite brought about much lower changes in CD amplitudes than P680 oxidation. In this case, only a small asymmetric bleaching at 680 and 668 nm in the red region and a bleaching at 445, 435 and 416 nm in the Soret region has been detected. Therefore, we suppose that the contribution of the Pheo of the primary acceptor to the total CD signal of RC is negligible. In contrast to the oxidation of primary donor, the light-induced change in the CD spectrum upon primary acceptor reduction was strongly temperature-dependent. The reversible CD bleaching was completely inhibited below 200 K, although the reduced Pheo was accumulated even at a temperature of 77 K. Since the temperature does not influence the excitonic interaction, the temperature dependence of the CD changes upon Pheo reduction does not support the model of Pheo excitonically interacting with the other chlorophylls (Chl) of the RC. We propose that Pheo should not be considered as a part of a multimer model.
Keywords: Photosystem II Protein Complex; Photosynthetic Reaction Center Complex Proteins; fotosyntetická reakční centra (proteinové komplexy); oxidace-redukce; cirkulární dichroismus; fotosystém II (proteinový komplex); Circular Dichroism; Oxidation-Reduction